Metaphysics, soul, and ethics in ancient thought : themes from the work of Richard Sorabji - Salles, Ricardo (Clarendon Press ; Oxford University Press, 2005)
Leading figures in ancient philosophy present eighteen original papers on three key themes in the work of Richard Sorabji. The papers dealing with Metaphysics range from Democritus to Numenius on basic questions about the structure and nature of reality: necessitation, properties, and time. The section on Soul includes one paper on the individuation of souls in Plato and five papers on Aristotle's and Aristotelian theories of cognition, with a special emphasis on perception. Thesection devoted to Ethics concentrates upon Stoicism and the complex views the Stoics held on such topics as motivati.